Impact of Demonetization on Indian Economy: Examining the Effects of Demonetization on Various Sectors of the Indian Economy (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper has to analyze the impact of demonetization on Indian Economy. The present paper shows the impact on different sectors of economy whether it is positive or negative. Before 2016, the Indian currency was demonetized first time in 1946 and second time in 1978. Then on 8thNovember, 2016 currency is demonetized third time by the Modi Government. Secondary data is collected for this paper. The required data is collected for this paper. The required data is collected from the published sources like magazines, newspaper, reports. The study covers the impact of demonetization Inflation, Gross Domestic product (GDP), Export-Import and other areas which are affected fro, it. This paper presents the results which come in India after demonetization and some results are more useful which helps in the growth of India.